2020
DOI: 10.15407/ugz2020.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Nitrate Vulnerable Zones Designation in Surface and Ground Water

Abstract: The article presents the national methodology for the identification of vulnerable areas to pollution of surface and ground water by nutrients compounds. The designation of nitrate vulnerable zones is an effective tool to reduce the impact of agricultural activities on water pollution by nutrients and is used for managing of diffuse pollution within river basins to achieve “good” ecological status. The analysis of heterogeneity of natural conditions in Ukraine and intensity of agricultural activity allows to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To calculate the risk, it was proposed to use the maximum permissible concentration of individual nitrogen compounds, and the threshold value (sensitivity coefficient k n =11.3 mgN/dm 3 ) for the sum of nitrogen concentrations. This indicator is the property of the implementation of the provisions of the nitrate directive in different countries, including Ukraine [39]. A close linear relationship between the values of R` and k n was established for individual rivers by year (Fig.…”
Section: Discussion Of the Research Results Of The Development Of A Methods For Assessing The Risk Of Surface Water Pollution By Nitrogenmentioning
confidence: 77%
“…To calculate the risk, it was proposed to use the maximum permissible concentration of individual nitrogen compounds, and the threshold value (sensitivity coefficient k n =11.3 mgN/dm 3 ) for the sum of nitrogen concentrations. This indicator is the property of the implementation of the provisions of the nitrate directive in different countries, including Ukraine [39]. A close linear relationship between the values of R` and k n was established for individual rivers by year (Fig.…”
Section: Discussion Of the Research Results Of The Development Of A Methods For Assessing The Risk Of Surface Water Pollution By Nitrogenmentioning
confidence: 77%
“…Previous studies have revealed the interactive effects of increased nutrient concentrations and warming in promoting the frequency and magnitude of cyanobacterial blooms [1][2][3][4][5][6][7].…”
Section: Purpose and Methodsmentioning
confidence: 99%
“…The strongest development of lands is overtaking 70% and for the FAO grants it is one of the most important light, but the need for intensification of vibration stimulating producers to a great stagnation quantity of mineral additives. People faced a serious challenge wiping between the viability of food products and the fermentation of waters [7].…”
Section: Introductionmentioning
confidence: 99%